Interaksi Kekuasaan Adat dan Negara dalam Perspektif Masyarakat Bali Kuno Tenganan Pegringsingan - I Wayan Suyadnya (Universitas Udayana, 2021)
Bali possesses a unique and complex form of village governance. In addition to the two village forms of desa dinas (handling formal administration affairs) and desa adat (handling customary, religious, and cultural affairs), an Old-Balinese village possesses a governance system that is relatively autonomous from state authority intervention. This article discusses how the Old-Balinese village of Tenganan Pegringsingan in Karangasem Regency, Bali maintains its autonomy and conducts negotiations with government regulations. The study is focused on the impact of central and regional government regulations such as Villages Law 6/2014 and Bali Provincial regulation 4/2019 on customary villages in Bali. Data were taken from an ethnographic study conducted through field research in 2003 and 2010. The study concludes that the Tenganan Pegringsingan village conducts continuous negotiation as a form of strengthening its identity and harmonizing the formal relationship with the state through the regional government. This article contributes to the understanding of the rich and complexity of traditional, social, and cultural living in the modern Bali.